2019
DOI: 10.1097/j.pain.0000000000001763
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the use of opioids by patients with chronic pain: an effectiveness study with long-term follow-up

Abstract: This study addresses the problem of long-term opioid use by chronic pain patients. The study involved a secondary analysis of unanalyzed data from a published study of 2 versions of cognitive-behavioural therapy-based interdisciplinary treatment for chronic pain. In this study, we examined whether the use of opioids by 140 chronic pain patients could be ceased sustainably over 12 months after participation in the comprehensive interdisciplinary pain management program aimed at enhancing pain self-management. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Among 3,155 potentially relevant citations, we included 49 studies-1 systematic review (Frank et al), 8 34 studies included in that systematic review,, and 14 new studies identified in our literature search. [50][51][52][53][54][55][56][57][58][59][60][61][62][63] A total of 40,245 patients are included in the 14 new studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 3,155 potentially relevant citations, we included 49 studies-1 systematic review (Frank et al), 8 34 studies included in that systematic review,, and 14 new studies identified in our literature search. [50][51][52][53][54][55][56][57][58][59][60][61][62][63] A total of 40,245 patients are included in the 14 new studies.…”
Section: Resultsmentioning
confidence: 99%
“…We prioritized evidence synthesis of: 1) studies conducted in a VHA setting or other outpatient settings; 2) studies that addressed serious harms such as overdose and suicide; and 3) studies that included enough detail regarding patient and tapering characteristics to evaluate the applicability of findings to VHA populations and settings. Nineteen studies (Table 1) (2 RCTs, 18, 50 6 controlled observational studies, 54,56,[60][61][62][63] and 11 uncontrolled observational studies) 27,30,32,34,36,40,55,[57][58][59]65 met these criteria, which we refer to as "prioritized studies." The remaining studies either had low applicability to VHA or outpatient settings or included patients or interventions that were not well-described.…”
Section: Resultsmentioning
confidence: 99%
“…[42] Furthermore, training patients to use pain self-management strategies was able to significantly reduce long-term opioid use in patients with chronic pain. [43] Enhanced continuing pain education is therefore essential for health care professionals, to fill gaps in their knowledge and increase competencies related to pain management.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data suggest that when patients volunteer to taper, a patient-centered, multimodal approach involving pain education, nonpharmacological pain self-management strategies, routine follow-up with a trusted health care provider, and support for coping with pain and withdrawal symptoms may improve outcomes [9,[14][15][16][17][18]. However, patients face a number of obstacles in accessing comprehensive opioid tapering support.…”
Section: Introductionmentioning
confidence: 99%